GURU TEUPA KUJANG “ABAH WAHYU”: SEBUAH SEJARAH LISAN - Sri Wulan; Muthia Nurhayati (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2021)
This study aims to reveal the knowledge possessed by a Teupa teacher to share information about what and how to make Kujang which is widely known as a typical weapon from West Java. The Teupa teacher who was an informant in this study was Wahyu Affandi Suradinata from Bogor, better known as Abah Wahyu. Through a qualitative method with a descriptive approach it is hoped that it can convey straightforwardly about the profession of a Teupa Kujang Teacher. In-depth interviews were conducted in November 2014 and then supplemented with other supporting references. The results of the study show that the dedication of Abah Wahyu for 26 years made Kujang qualified as a Teupa Teacher so that he could become an example and worthy of being emulated by the next generation, then it is hoped that there will be a successor so that the cultural wealth especially related to Kujang does not become extinct. Through this study, we are really hope to capture the oral history of a Teupa Kujang teacher that is useful for the general public and cultural enthusiasts in particular so the preservation of the existence of Kujang can be maintained.